2014
DOI: 10.4103/2230-8210.131169
|View full text |Cite
|
Sign up to set email alerts
|

Glucose homeostasis in Egyptian children and adolescents with β-Thalassemia major: Relationship to oxidative stress

Abstract: Background:Oxidative stress in children with β-thalassemia may contribute to shortened life span of erythrocytes and endocrinal abnormalities.Aim:This study was aimed to evaluate glucose homeostasis in Egyptian children and adolescents with β-thalassemia major and its relation to oxidative stress.Materials and Methods:Sixty children and adolescents with β-thalassemia major were studied in comparison to 30 healthy age and sex-matched subjects. Detailed medical history, thorough clinical examination, and laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…The prevalence of glucose metabolism dysregulation found in our study was much higher than 13%, which was reported by Metwalley et al . (2014) involving 60 thalassaemic children . This wide variation in prevalence was multifactorial: dependent on the duration of blood transfusion, degree of iron load, organ dysfunction, type of chelators, compliance to therapy and age of patient .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of glucose metabolism dysregulation found in our study was much higher than 13%, which was reported by Metwalley et al . (2014) involving 60 thalassaemic children . This wide variation in prevalence was multifactorial: dependent on the duration of blood transfusion, degree of iron load, organ dysfunction, type of chelators, compliance to therapy and age of patient .…”
Section: Discussionmentioning
confidence: 99%
“…Just over one‐quarter (27.5%) of patients with Hb H disease had insulin resistance, as measured by HOMA‐IR that was significantly related to obesity, but not with iron overload or anemia. Insulin resistance has been extensively studied among patients with TDT (mainly β‐thalassemia major), and it is known to be related to the severity of iron overload . Meanwhile, studies in NTDT patients (mostly β‐thalassemia intermedia) with iron overload reported variable prevalence of impaired glucose tolerance and DM .…”
Section: Discussionmentioning
confidence: 99%
“…Metwalley and El‐Saied evaluated glucose homeostasis in Egyptian children and adolescents with β‐TM. The prevalence of diabetes was 5% (3 of 60) and IGT was 8% (5 of 60).…”
Section: Discussionmentioning
confidence: 99%
“…The difference was more evident in patients with abnormal OGTT and those who did not receive chelation or were on irregular chelation therapy. Therefore, they suggested regular iron chelation for thalassemia patients to improve glucose hemostasis and recommended that OGTT and HOMA‐IR should be an integral part of the long‐term follow‐up of children and adolescents with β‐TM …”
Section: Discussionmentioning
confidence: 99%